Lispirurus nom. nov. for Sicarius Li, 1934 (Nematoda, Spirurida) preoccupied by Sicarius Walckenaer, 1847 (Arthropoda, Arachnida) - Ederli, Nicole Brand (Zootaxa, 2017)
The generic name Lispirurus Ederli, nom. nov. for Sicarius Li, 1934 (Nematoda, Spirurida), is a homonym of the generic name Sicarius Walckenaer, 1847 (Arthropoda, Arachnida). The genus Sicarius Walckenaer, 1847 was originally erected for spiders, commonly known as six-eyed sand spiders, and contains 25 species, while the genus Sicarius Li, 1934 was erected to include some Habronematinae nematode species, which some of them were transferred to the genus Procyrnea. Thus, actually, the new genus Lispirurus, is composed of a total of 4 species, with L. dipterum as the type species.